2016
DOI: 10.4172/2168-9873.1000243
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sub-Zero Treatment on the Wear Resistance of P/M Tool Steels

Abstract: Sub-zero treatment of tool steels is included within the cycle of conventional heat treatment. This kind of heat treatment has been reported to improve wear resistance of tools. The improvement is attributed to precipitation of fine carbide particles, but is depending on a number of the other factors as well. This paper follows the previous works, in which the effect of sub-zero treatment on the mechanical and structural properties of P/M tool steels was evaluated. Two types of P/M cold work tool steels were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…25 Effect of sub-zero treatment on the wear resistance of powder metal (P/M) tool steels has been investigated by Sobotova and colleagues, significant results have been achieved on wear resistance of P/M tool steels. 26 Xiao-Hui Lu and colleagues investigated the effects of subzero celsius treatment of retained austenite in bearing steel and results showed that the activation energy of retained austenite decomposition slightly increased through subzero celsius treatment and tempering. 27 Effect of heat treatment on the bimetallic plates has been investigated by O ¨zdemir 28 and also by Hao Li and colleagues; 29 both investigations presented significant results in terms of hardness, toughness, and good interface.…”
Section: Introductionmentioning
confidence: 99%
“…25 Effect of sub-zero treatment on the wear resistance of powder metal (P/M) tool steels has been investigated by Sobotova and colleagues, significant results have been achieved on wear resistance of P/M tool steels. 26 Xiao-Hui Lu and colleagues investigated the effects of subzero celsius treatment of retained austenite in bearing steel and results showed that the activation energy of retained austenite decomposition slightly increased through subzero celsius treatment and tempering. 27 Effect of heat treatment on the bimetallic plates has been investigated by O ¨zdemir 28 and also by Hao Li and colleagues; 29 both investigations presented significant results in terms of hardness, toughness, and good interface.…”
Section: Introductionmentioning
confidence: 99%